2010
DOI: 10.1002/crat.201000117
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effects accompanying near equilibrium vapour growth of solid solution crystals of the types IV‐VI and II‐VI

Abstract: Near equilibrium evaporation-condensation in a sealed ampoule leads to almost full compositional reproduction of a solid solution if it consists of components having comparable vapour pressures; this can be qualitatively interpreted by domination of entropy increase. Nevertheless, even vestigial separation requires closer characteristics, since it may prove crucial -particularly for properties of semiconducting solid solutions. Maximum component separation allowed by a small temperature difference is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The difference in x of 0.02 between the produced crystal and the part of remainders is larger than usually observed for the SSVG method. We attribute it to considerably smaller volatility of ZnTe than of CdTe and also (stronger than usual) deviation of the ampoule interior from isothermal character -it was shown that the limit of separation degree in a closed, near equilibrium system is a growing function of deviation from isothermal conditions [32].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The difference in x of 0.02 between the produced crystal and the part of remainders is larger than usually observed for the SSVG method. We attribute it to considerably smaller volatility of ZnTe than of CdTe and also (stronger than usual) deviation of the ampoule interior from isothermal character -it was shown that the limit of separation degree in a closed, near equilibrium system is a growing function of deviation from isothermal conditions [32].…”
Section: Resultsmentioning
confidence: 91%
“…The method of self-selecting vapour growth SSVG, which is based on formation of specific temperature field [31], provides most favourable conditions for undisturbed vapour growth of monocrystals, since it ensures best reduction of influence of any foreign material on the growing crystal. Simultaneously, a near isothermal, closed system ensures in general the lowest level of compositional gradients [32], when solid solution crystals are grown. Therefore, compositional differences remain near to the detection limit of most sensitive analytical techniques.…”
mentioning
confidence: 99%
“…e σ , na qual σ, o parâmetro exponencial da equação de Gibbs-Thomson, é deőnido por σ ≡ 2γVm rcRT , onde γ é o termo de energia de superfície para o CdTe, R é a constante universal dos gases, r C é o raio crítico, a partir do qual os PQs se formam, T é a temperatura do meio reacional e V m é o volume molar, que para o CdTe vale 38,711 cm 3 mol [71]. Para seguirmos adiante com o cálculo da concentração de equilíbrio, precisamos determinar primeiramente o raio crítico.…”
Section: Evolução Temporal Da Distribuição De Tamanhos E Do Tamanho M...unclassified